Анализа корелације цитокина Тх1/Тх2 и показатеља јетрене фиброзе код пацијената са хроничним хепатитисом Б: Цитокини Тх1/Тх2 и показатељи јетрене фиброзе код хроничног хепатитиса Б - Yu, Chun; Chen, Meiling; Han, Xiaonan; Feng, Yu-Hang; Sun, Hongwei; Yang, Hong (Journal of Medical Biochemistry, 2025)
Objective: To investigate the potential therapeutic benefits of autoimmune antibody detection in individuals suffering from chronic hepatitis B. Methods: For the observation group, 102 patients with chronic hepatitis B who were admitted between March 2022 and March 2025 were chosen. Additionally, the control group consisted of 102 healthy people who were examined throughout the same time period. The two groups’ autoimmune antibodies were identified, and patients in the observation group with positive and negative autoimmune antibodies were compared in terms of their liver function, liver fibrosis markers, and cytokine levels. Results: The total positive rate of autoimmune antibodies in the observation group was 26.47%, whereas it was 3.92% in the control group (P<0.05). Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were noticeably greater in the observation group’s patients with positive autoimmune antibodies than in those with negative antibodies. However, the albumin (ALB) and total protein (TP) levels were much lower than those of patients with negative antibodies. A statistically significant difference was observed (P<0.05). Type III procollagen (PCIII), hyaluronidase (HA), and the levels of laminin (LN) were statistically significant (P<0.05) higher in individuals with positive autoimmune antibodies than in those with negative antibodies. Patients with positive autoimmune antibodies had considerably higher levels of interleukin-4 (IL-4), interleukin-10 (IL-10), and interleukin-6 (IL-6) than patients with negative antibodies. Patients with negative antibodies had significantly higher levels of interferon-γ (IFN-γ) (P < 0.05). Conclusion: Autoimmune antibodies are present in patients with chronic hepatitis B, which influence liver fibrosis indicators and related cytokines. The identification of autoimmune antibodies in chronic hepatitis B patients can serve as a guide for evaluating the illness and determining prognosis.